2020
DOI: 10.1007/s10008-020-04522-4
|View full text |Cite
|
Sign up to set email alerts
|

Doped (Nd,Ba)FeO3 oxides as potential electrodes for symmetrically designed protonic ceramic electrochemical cells

Abstract: The design of new electrode materials with high redox stability has great potential for the fabrication of solid oxide fuel and electrolysis cells having a symmetrical configuration; such a configuration is particularly promising in terms of economic and technological factors due to involving a reduced number of functional materials and technological steps. Under the framework of the present study, we developed new Nd 1-x Ba x Fe 0.9 M 0.1 O 3-δ materials (where M = Cu or Ni, x = 0.4 or 0.6), characterizing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…It was found that the ORR activity of our BCYF2 cathode in proton-conducting electrolyte surpassed most of the Fe-based cathodes reported so far. [57][58][59][60][61][62][63][64] In addition, the BCYF2 also displayed a superior ORR stability in terms of the ASR value obtained in the BZCYYbbased symmetrical cell for 180 h at 600 C in wet air (Fig. S8 †), highlighting its superiority as an efficient and durable cathode for PCFCs.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the ORR activity of our BCYF2 cathode in proton-conducting electrolyte surpassed most of the Fe-based cathodes reported so far. [57][58][59][60][61][62][63][64] In addition, the BCYF2 also displayed a superior ORR stability in terms of the ASR value obtained in the BZCYYbbased symmetrical cell for 180 h at 600 C in wet air (Fig. S8 †), highlighting its superiority as an efficient and durable cathode for PCFCs.…”
Section: Resultsmentioning
confidence: 99%
“…Other examples are LaFeO 3 -, SrFeO 3 -, and BaFeO 3 -based complex oxides, which display meaningful n-type conductivity values coming from the reduction of Fe 3+ -ions: 83–85 …”
Section: Electronic Transport Of Individual Proton-conducting Materialsmentioning
confidence: 99%
“…Pr0.4Sr0.6Co0.2Fe0.7Mo0.1O3−, (La0.6Sr0.4)0.95Fe0.8Ni0.1Mo0.1O3-δ and Pr0.6Ba0.4Fe0.8Cu0.2O3−δ have been used for the electrochemical production of ethylene from ethane in a protonic SOC at 750 o C and ammonia at low temperature, respectively [317][318][319] . Along with the development of protonic conducting SOCs operating at low temperatures [320][321][322] , the special properties of iron-based materials will find more opportunities to be used to balance the stability and performance, especially in symmetrical cells 139,323 .…”
Section: Discussionmentioning
confidence: 99%